Zeitgenössische Fotografie aus Spanien : Galerie Wolfgang Gmyrek - Galería Helga de Alvear. - Ribalta, Jorge; Galerie Wolfgang Gmyrek, Düsseldorf (Düsseldorf : Galerie Wolfgang Gmyrek, 1998)
Canogar, Daniel ; Fontcuberta, Joan ; Palacín, Mabel ; Valldosera, Eulàlia ; Vallhonrat, Javier
Zeitgenössische Fotografie aus Spanien, Galerie Wolfgang Gmyrek, Düsseldorf, am 23. Oktober 1998
kunstcatalogus
Keywords: Spanje